Long-term business implications of Russia's war in Ukraine - Stanislav Markus (Asian Business & Management, 2022)
Following its invasion of Ukraine, Russia's macroeconomic stability will worsen; foreign trade and Russia-bound investment will dry up; and human capital will become scarce. Russia will not fully compensate these losses with increased economic engagement with China, with particular deficiencies likely in high-tech areas for Russia. Import substitution is also unlikely to allow Russia to innovate its way out of economic isolation or escape the resource curse. As Kremlin-connected elites further dominate the impoverished economy, crony state capitalism and kleptocracy will rise. The global repercussions of Russia's war will include commodity shocks and the attendant supply chain disruptions and inflationary pressures. In terms of FDI, the global industries in energy, auto, and consumer goods will be particularly affected. The loss of the Russian market will be less critical to sales revenues. Structurally, Russia's forced decoupling from the global economy may lead to the fragmentation of global financial infrastructure and the formation of economically contained blocks.
Keywords: 650; Geopolitics; Russian war; Sanctions; De-globalization; Business climate